Impacts of mining on local fauna of wildlife in District Mardan & District Mohmand Khyber Pakhtunkhwa Pakistan - Rehman, G.; khattak, I.; Hamayun, M.; Rahman, A.; Haseeb, M.; Umar, M.; Ali, S.; Iftikhar; Shams, W. A.; Pervaiz, R. (Brazilian journal of biology, 2024)
Abstract Mining is vital for human sustenance and a crucial sector in the state economy. However, its impacts on the environment and biodiversity cannot be underestimated. Which are potent to the attract government’s attention. Environment and wildlife are subject to the harmful impacts of mining and its related activities. In this study, districts, namely Mardan and Mohmand have been targeted with respect to mining impacts. The assessment was carried out on wildlife adversely affected by the mining sector. The fauna has been keenly observed to bring the calculated risks and threat perception of the regional wildlife. Total 9 species of mammals, 21 species of birds, were recorded in District Mardan. While in District Mohmand 2 species of mammals, 9 species of birds, and 4 species of reptiles were studied. The Study explored that mining primarily responsible for land degradation. Which lead to food and agriculture losses. Several other factors like blasting, pollution, hunting, deforestation, habitat loss was also observed. Deforestation surfaced one of the major causes for extinction of fauna in the said region. preemptive measures are needed to seize the man-made catastrophe. Resumo A mineração é vital para o sustento humano e um setor crucial na economia do Estado. No entanto, seus impactos sobre o meio ambiente e a biodiversidade não podem ser subestimados, visto serem potentes para atrair a atenção do governo. O meio ambiente e a vida selvagem estão sujeitos aos impactos prejudiciais da mineração e de suas atividades relacionadas. Neste estudo, os distritos, nomeadamente Mardan e Mohmand, foram selecionados no que diz respeito aos impactos da mineração. A avaliação foi realizada em animais selvagens afetados negativamente pelo setor de mineração. A fauna tem sido observada atentamente para trazer os riscos calculados e a percepção de ameaça à vida selvagem regional. Um total de nove espécies de mamíferos, 21 espécies de pássaros, foi registrado no Distrito Mardan. Enquanto no Distrito Mohmand, duas espécies de mamíferos, nove espécies de pássaros e quatro espécies de répteis foram estudadas. O estudo explorou essa mineração que é principalmente responsável pela degradação do solo, acarretando perdas de alimentos e na agricultura. Vários outros fatores como explosões, poluição, caça, desmatamento, perda de habitat também foram observados. O desmatamento veio à tona como uma das principais causas de extinção da fauna da região, e tem-se que medidas preventivas são necessárias para dimensionar a catástrofe provocada pelo homem.